2023
DOI: 10.3390/vaccines11101609
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Microbiota in Modulating Vaccine Immune Response: A Long Way to Go

Francesca Romana Ponziani,
Gaetano Coppola,
Pierluigi Rio
et al.

Abstract: Vaccine immunogenicity still represents an unmet need in specific populations, such as people from developing countries and “edge populations”. Both intrinsic and extrinsic factors, such as the environment, age, and dietary habits, influence cellular and humoral immune responses. The human microbiota represents a potential key to understanding how these factors impact the immune response to vaccination, with its modulation being a potential step to address vaccine immunogenicity. The aim of this narrative revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 149 publications
0
4
0
Order By: Relevance
“… 45–47 It has also been shown that having malnutrition as well as polioseronegativity may cause additional burden to the individual and lead to worse functional outcomes. 48 , 49 …”
Section: Discussionmentioning
confidence: 99%
“… 45–47 It has also been shown that having malnutrition as well as polioseronegativity may cause additional burden to the individual and lead to worse functional outcomes. 48 , 49 …”
Section: Discussionmentioning
confidence: 99%
“…Understanding the immunological interplay between sex, vaccines, and microbiota could make the latter a potential target of novel approaches to improve vaccine immunogenicity [ 119 ]. In the future, bioengineering approaches targeting the GM in a sex-specific manner may increase the immune responses to vaccines.…”
Section: Gut Microbiota Gender and Vaccinesmentioning
confidence: 99%
“…Considering the great impact of gut-liver axis dysfunction in cirrhosis on the immune response, a role in the immunization process appears to be intuitive. Indeed, emerging evidence underscores the potential role of microbiota imbalance in modulating the efficacy of vaccination responses [161]. However, whether these alterations lead to impaired immunization in patients with cirrhosis remains unclear, and further investigations are needed.…”
Section: Vaccination Response and Gut-liver Axis In Cirrhosismentioning
confidence: 99%